Ulster Presbyterianism as A Popular Religious Culture, 1750–1860 - Holmes, Andrew R. (Studies in church history, 2006)
Both the study of popular religion and popular culture in the eighteenth and nineteenth centuries suffer from a number of methodological and definitional problems. Historians of religion often assume that popular religion is synonymous with superstitious beliefs that have little or no relation to confessional orthodoxy. It is further claimed that during the nineteenth century superstition was abandoned as a consequence of the modernization of society and the imposition of respectable behaviour. Complementing this tendency, historians of popular culture in this period have generally ignored the religious aspects of everyday life and describe culture primarily in secular terms. This has much to do with the tendency to adopt, consciously or otherwise, a world-view that automatically assumes the subservience of religion to culture in the modern world. According to this view, once the events of the Enlightenment and the French Revolution had cast their spell, organized religion and personal religious faith were jettisoned, often in favour of the nebulous term ‘culture’, and a wedge driven between the sacred and secular. Given the overwhelming amount of evidence to the contrary, it is obvious that this tendency significantly hinders our understanding of the everyday lives and thoughts of our ancestors, especially in the Irish and specifically Ulster context where religion still has an importance that some fail to credit with sufficient patience, let alone understanding. As a result of these problems, the study of popular religion in the modern period lags well behind the advances made by historians of religion in sixteenth- and seventeenth-century Europe.